2017
DOI: 10.1021/acs.inorgchem.7b01177
|View full text |Cite
|
Sign up to set email alerts
|

Ullmann Reaction Catalyzed by Heterogeneous Mesoporous Copper/Manganese Oxide: A Kinetic and Mechanistic Analysis

Abstract: A heterogeneous copper oxide supported on mesoporous manganese oxide (meso Cu/MnO) was explored for Ullmann-type cross-coupling reactions. An inverse micelle-templated evaporation-induced self-assembly method with in situ addition of copper was adopted to synthesize the mesoporous catalyst. Broad substrate scope and excellent functional group tolerability in C-O, C-N, and C-S bond formation reactions were observed using the optimized reaction conditions. The catalytic protocol was ligand free, and the catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…A possible mechanism is proposed for the synthesis of diaryl ether that is consistent with the literature . Firstly, Fe 3 O 4 /CS‐Cu NPs inserts in the aryl halide bond via oxidative addition reaction (I).…”
Section: Resultssupporting
confidence: 73%
“…A possible mechanism is proposed for the synthesis of diaryl ether that is consistent with the literature . Firstly, Fe 3 O 4 /CS‐Cu NPs inserts in the aryl halide bond via oxidative addition reaction (I).…”
Section: Resultssupporting
confidence: 73%
“…In Table 4, the catalytic activity of our present catalytic system with various reported heterogeneous catalysts in the N-arylation of iodobenzene with aniline is compared. [77][78][79] Our synthesized CuNPs@Q-POP catalyst demonstrates better or comparable performance over reported catalysts. It is more likely, high catalytic activity and durability of our catalyst can be ascribed to the extraordinary stability of the polymeric network as a support along with large pore size playing the role of nanoreactor and the facilitated diffusion of reactants inside the polymeric network of catalyst.…”
Section: The Comparison Of Our Methods With Some Reported Methods In Thmentioning
confidence: 72%
“…The Ullmann coupling reaction is a classic metal-catalyzed synthetic method for forming C–C bonds where two aryl halides are coupled over a copper catalyst to form a biaryl molecule. , The original Ullmann reaction traditionally required stoichiometric amounts of copper and aryl halides in order to proceed. However, modern iterations of the reaction have found that catalytic amounts of copper bound ligands and a wide range of copper species can be used to promote the reaction. Unlike other metal-mediated reactions, the Ullmann mechanism is not as fully understood despite its widespread study and application. This is due to its unpredictable selectivity coupled with its sensitivity to functional groups and the need for extreme reaction conditions. …”
Section: Introductionmentioning
confidence: 99%